Elucidating reaction dynamics in lithium–sulfur batteries via operando X-ray diffraction of hollow carbon sphere hosts - Deaglán Bowman; Erlantz Lizundia; David McNulty (Communications Materials)
Abstract Lithium–sulfur (Li–S) batteries offer a promising route to affordable, clean, and high-performance energy storage. However, their widespread adoption is hindered by complex and inefficient charge storage mechanisms. Hollow carbon spheres have demonstrated improved Li–S cell performance, yet their specific effect on sulfur/Li2S conversion dynamics remains insufficiently understood. Here, we present a facile synthesis method for glucose-derived hollow carbon spheres, delivering a high specific charge of 1159 mAh g−1 (C/10) and a reversible specific charge of 510 mAh g−1 after 500 cycles (C/5). Using operando X-ray diffraction, we investigate their influence on Li–S reaction dynamics. Analysis of relative peak intensities and full width at half-maximum indicates a plateau in Li2S crystallite size at 60% depth of discharge. This supports the formation of a disproportionation-driven amorphous polysulphide matrix that restricts Li2S crystallite growth and discharge capacity. Electro-crystallisation induces notable changes to sulfur upon charge, including shifts in allotropes and crystallite orientation.